8r-2r(r+5)=5(2r-6)-8

Simple and best practice solution for 8r-2r(r+5)=5(2r-6)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8r-2r(r+5)=5(2r-6)-8 equation:



8r-2r(r+5)=5(2r-6)-8
We move all terms to the left:
8r-2r(r+5)-(5(2r-6)-8)=0
We multiply parentheses
-2r^2+8r-10r-(5(2r-6)-8)=0
We calculate terms in parentheses: -(5(2r-6)-8), so:
5(2r-6)-8
We multiply parentheses
10r-30-8
We add all the numbers together, and all the variables
10r-38
Back to the equation:
-(10r-38)
We add all the numbers together, and all the variables
-2r^2-2r-(10r-38)=0
We get rid of parentheses
-2r^2-2r-10r+38=0
We add all the numbers together, and all the variables
-2r^2-12r+38=0
a = -2; b = -12; c = +38;
Δ = b2-4ac
Δ = -122-4·(-2)·38
Δ = 448
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{448}=\sqrt{64*7}=\sqrt{64}*\sqrt{7}=8\sqrt{7}$
$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-8\sqrt{7}}{2*-2}=\frac{12-8\sqrt{7}}{-4} $
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+8\sqrt{7}}{2*-2}=\frac{12+8\sqrt{7}}{-4} $

See similar equations:

| (x-1)(x-1)=(x+22)(x+2) | | -6/7+h=1/6 | | 12x^2+4=22x | | (x-3)/4=(x-2)/5 | | -9x+58=-6x+7 | | 1/2x+5=3/4 | | 4a+2-5a=3a+6-40 | | 8x+1=6x+41 | | 5x+500=2x+550 | | -4(3r-4)=32 | | 12x-26=-5x-6+13x | | 2c-4+5c=-25 | | -5(2n+1)-n=-82 | | -7x-28=-3x | | 5c+9=16 | | 5-5h/50=0.1 | | 9x+68=4x-7 | | 7=-(2h-18) | | 12x-2x+12-4=100 | | 2/3+x/4=1/2-x/2 | | 4x-(3x+4)=2x-12 | | 2x-8/7=6/7 | | (60-2x)(80-2x)=0 | | -3x-6+9=27 | | 3w*w=144 | | 40-3•x=-8 | | 2z+8-z=5z-44 | | -1x/6+x/6=6 | | 8+4n=7n+2 | | 6y+8=3y+89 | | -x-2(x-5)=31 | | (4x+1)÷3=11 |

Equations solver categories